Increasing inflationary T-cell responses following transient depletion of MCMV-specific memory T cells - Sims, S; Bolinger, B; Klenerman, P (Wiley, 2015)
Vol 45 (1) 2015, http://onlinelibrary.wiley.com/doi/10.1002/eji.201445016/abstract Increasing inflationary T-cell responses following transient depletion of MCMV-specific memory T cells; Stuart Sims and Paul Klenerman. In the above mentioned article the authors neglected to include the name of another author. The corrected authors’ affiliation list is shown below: Stuart Sims (Peter Medawar Building for Pathogen Research, University of Oxford, Oxford, UK), Beatrice Bolinger (Biozentrum, University of Basel, Basel, Switzerland) and Paul Klenerman (Peter Medawar Building for Pathogen Research, University of Oxford, Oxford, UK)